Pemetaan Mitigasi Bencana, Deforestasi, dan Kebijakan Komunikasi Pemerintah: Implikasi bagi Sumatera Utara - Arya Fandhy; Prawira Yudha; Raissa Adhwa Hanafiah; Rahmanita Ginting (Jurnal Indonesia : Manajemen Informatika dan Komunikasi, 2026)
This study aims to analyze the network structure, theme development, and density of disaster mitigation, deforestation, and government communication policies, as well as examine its implications for socio-ecological vulnerability conditions in North Sumatra. This research method uses a quantitative approach with a bibliometric design through the metadata analysis of publications for the 2020–2025 period, each as many as 1291 articles for the theme of disaster mitigation, deforestation, and government communication policies, as well as 59 disaster-related articles in North Sumatra, using VOSviewer to map network visualization, overlay, and density. The results of this study reveal that the dominance of policy clusters as a link between deforestation and flood risk shows that the effectiveness of disaster mitigation in North Sumatra is highly determined by the direction, consistency, and integration of development policies. The findings of the study density on policy and land use issues directly imply the need to tighten licensing, control deforestation, and spatial and watershed planning as mitigation policy priorities. Meanwhile, the shift in theme towards more specific flood risk assessments underscores the need for prevention and data-driven policies, which must be strengthened through transparent and participatory government risk communication in order to transform risk knowledge into long-term vulnerability reduction collective action.